Tradisi Ritual Tolak Bala Bulan Safar Masyarakat Jawa di Pematang Muawan, Rokan Hilir, Riau. - Siti Nur Aisyah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The implementation of the ritual tradition of rejecting reinforcements in the month of Safar in the Javanese community of Pematang Muawan, Riau, which is held every year is a form of traditional ceremony carried out with the meaning of avoiding the troubles that come in the month of Safar. It is stated that the month of Safar is negative pole. The purpose of this research is to find out the implementation of the ritual tradition of rejecting reinforcements the month of Safar and the factors that influence the Javanese people of Pematang Muawan in carrying out the ritual tradition of rejecting the reinforcements of the month of Safar or what is called Safaran. This type of research is empirical research (field) and the data collected is the result of interviews with informants and is supported by the appropriate literature. This research is a descriptive analysis and the approach in this study uses a sociological approach. The results of the study show that the Javanese people of Pematang Muawan believe in repelling disaster reinforcements and disturbances by supernatural beings by carrying out prayers to drive away reinforcements which are carried out in congregation with the provisions that apply in the field or mosque, followed by dhikr, prayer lidhaf'il bala , cutting cones, offerings, purification in the morning on objects used for work and ending with a safar bath before midday prayers or midday and the factors that influence the community in carrying out the ritual tradition of rejecting the reinforcements of the safah month are customary, fanatical and internal factors that arise because of anxiety or fear of the impacts arising from not carrying out the safaran tradition . It is hoped that this simple writing will be able to provide information to the reader about the tradition of the ritual of rejecting the bala month of Safar which is carried out mainly by the Javanese people of Pematang Muawan.